A Comparison of Three Different Physiotherapy Modalities Used in the Physiotherapy of Burns - (:unkn) unknown (OXFORD UNIV PRESS, 2013)
The present study compared the effectiveness of matrix rhythm therapy, ultrasound treatment (UT), laser treatment (LT) used in the physiotherapy of burns. The study was conducted at the Wound and Burn Healing Center, Dr. Lutfi Krdar Kartal Education and Research Hospital (Turkey) from June 2009 to January 2012. The case series comprised 39 individuals with second- and third-degree upper-limb burns, whose burn traumas ended approximately 1 to 3 months previously. Participants were separated into three groups: matrix rhythm treatment (MRT), UT and LT; each group was also applied a treatment protocol including whirlpool and exercise. Pain, range of motion (ROM), muscular strength, skin elasticity, and sensory functions were evaluated before and after the treatment. Pressure sense and passive ROM were higher in the MRT group than in the LT group (P < .05). Pain was lower in the LT group than in the UT group, and passive ROM was higher in the UT group than the in LT group (P < .05). Active ROM was found to increase in all treatment groups, whereas passive ROM increased only in the MRT and UT groups; pressure sense increased only in the MRT group, and pain decreased only in the LT group (P < .05). MRT was found to be more effective in the restoration of sensory functions than LT, whereas LT was more effective in reducing pain than UT. No significant difference was observed in terms of skin elasticity according to the results of three treatment modalities. It is suggested that further research with more cases should be conducted to examine the long-term effect of treatment modalities.
Keywords: REHABILITATION; INJURY; LASER